Detection of Rickettsia spp. in ticks (Acari: Ixodidae) of domestic animals in Colombia - Rivera-Páez, Fredy A. [UNESP]; Martins, Thiago F.; Ossa-López, Paula A.; Sampieri, Bruno Rodrigues; Camargo-Mathias, Maria I. [UNESP] (Elsevier, 2018)
Rickettsiosis are emerging or re-emerging diseases, with a worldwide distribution associated to transmission by arthropod vectors. Rickettsia species belong to the spotted fever group (SFG) and are transmitted by hard ticks (Acari: Ixodidae) that may act as vectors and reservoirs. This study carried out a molecular detection of Rickettsia from 7 species of the family Ixodidae collected from domestic hosts by PCR amplification of fragments of the citrate synthase “gltA” gene and outer membrane protein “ompA” gene. Of the 204 samples analyzed, 11.3% (23) were positive for rickettsial infection. Three Rickettsia species belonging to the SFG were found, constituting the first reports of Rickettsia rickettsii in 2 departments of Colombia. Furthermore, we confirmed the first occurrence of Candidatus Rickettsia andeanae in Colombia, a species with an unknown pathogenic role in humans. These results raise awareness regarding the need to increase epidemiological control measures, as well as to consider new endemic regions in Colombia for Rocky Mountain spotted fever (RMSF).
Keywords: Candidatus Rickettsia andeanae; Endemic region; Rickettsia rickettsii.